1990
DOI: 10.1111/j.1469-8749.1990.tb16909.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Inflammatory and Demyelinating White‐matter Diseases of Childhood

Abstract: SUMMARY Magnetic resonance imaging (MRI) was performed on 36 children and two adults (with clinical presentation during childhood) with white‐matter disease of the central nervous system. Abnormalities were readily demonstrated in patients with multiple sclerosis, acute disseminated encephalomyelitis, leucodystrophies and subacute sclerosing panencephalitis: MRI demonstrated the extent and distribution of abnormalities more clearly than computed tomography for all these disorders. The abnormalities tended to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 32 publications
5
10
0
Order By: Relevance
“…Moreover, in agreement with previous reports, in children with ADEM, the lesions were usually bilateral, but asymmetrical, and highly variable in size, number, and gadolinium-enhancement [20,[24][25][26]. However, the most clear-cut difference between ADEM and MS concerned the localization of the lesions: periventricular lesions were common in MS, whereas lesions in the cortical/juxtacortical regions, basal ganglia, and thalamus were frequently observed in ADEM.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, in agreement with previous reports, in children with ADEM, the lesions were usually bilateral, but asymmetrical, and highly variable in size, number, and gadolinium-enhancement [20,[24][25][26]. However, the most clear-cut difference between ADEM and MS concerned the localization of the lesions: periventricular lesions were common in MS, whereas lesions in the cortical/juxtacortical regions, basal ganglia, and thalamus were frequently observed in ADEM.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, IgGOB appears to have a strong predictive value for the development of MS not only in adults but also in children. The MS CSF profile observed in our study is very similar to that recently observed in a cohort of 136 childhoodonset MS [24]. However, the simultaneous presence of a BBB damage and an increase in the lymphocyte count higher than 30 lymphocyte/μL was strongly suggestive of ADEM.…”
Section: Discussionsupporting
confidence: 88%
“…Data were centralized (Dr. A. Distefano) and independently analyzed; for the mean lesion count and qualitative features were analyzed, both in the brain and spinal cord, to create a proposed diagnostic model. A review of MRI scans was specifi cally targeted for the following: (i) absence of a diff use bilateral lesion pattern; (ii) presence of black holes; and (iii) presence of 2 or more periventricular lesions, as these criteria allowed distinction of patients with multiple sclerosis in the fi rst attack from patients with monophasic ADEM, with a sensitivity of 81 % and a specifi city of 95 % [21] .…”
Section: Methods: Imaging Studies and Evaluationmentioning
confidence: 99%
“…[1] It usually affects children or young adults. The diagnosis of SSPE is based on the characteristic clinical and electroencephalographic (EEG) findings (periodic complexes) and demonstration of elevated antibody titers against measles in the plasma and cerebrospinal fluid (CSF).…”
Section: Introductionmentioning
confidence: 99%